Pengembangan Website Harga Bapokting Real-time dengan Extreme Programming dan Integrasi API SILINDA - Ridwan Setiawan; Rina Parlina; Erwin Gunadhi (Journal of Applied Computer Science and Technology, 2025)
This study aims to implement the SILINDA API from the West Java Provincial Government on a prototype website to present real-time price data for Basic Necessities and Important Goods (Bapokting) in Garut Regency. This addresses the problem of reporting delays and potential data inaccuracies that arise from the manual process of reporting via WhatsApp and weekly recapitulation using Microsoft Excel. The system was developed using the Extreme Programming (XP) methodology, which includes the stages of planning, design, coding, and testing. System design utilizes Unified Modeling Language (UML), specifically use case and class diagrams. The implementation uses JavaScript with the React.js library for the frontend and Node.js with the Express.js framework for the backend. The result of this research is a website prototype that is synchronized with the SILINDA API to perform automatic price updates. System testing included unit testing with a black-box approach and acceptance testing using the System Usability Scale (SUS) method, which yielded an average score of 83, categorized as Grade A (Excellent) with an "Acceptable" level of acceptance. This research contributes a system that replaces the manual reporting process with a website synchronized with SILINDA, providing real-time data for the Disperindag ESDM, Garut Satu Data, and the general public. It also demonstrates the effectiveness of the XP method in building an adaptive system that is relevant to user needs.